Financial Feasibility Study of Toll Road Bogor-Serpong Via Parung - Jota, Astrid Laregan; Damayanti, Sylviana Maya (Journal of Business and Management, 2019)
Abstract. Indonesia's economic growth in 2010 to 2015 has been decreased due to the global economic slowdown. The structural changes can form of the development of export-oriented manufacturing industries, massive infrastructure development, and significantly improving the quality of Indonesian human resources. The feasibility study used as the base for the consideration whether the project is ready to go and as the base of the auction. The Bogor-Serpong via Parung toll road financial feasibility has been made by PT.XYZ, however, there is a time gap between the time they make the financial feasibility and the investing period that can make the financial assumption is not relevant. The author changes some assumption that is not relevant.The capital budgeting techniques used to determine the project are the payback period, Net Present Value (NPV), and Internal Rate of Return (IRR). The capital budgeting techniques result with the new assumption shows a payback period of Bogor-Serpong toll road is 12 year 9 month and 29 days, NPV is IDR 13,399,111million, and IRR is 16% which showed the project is possible. The result comparison of financial feasibility by PT.XYZ and financial feasibility using adjusted assumption showed the different result in NPV and payback period. PT.XYZ calculation shows the payback period is 13.39 years and NPV is IDR 13,399,111million. The private sector should be aware of the sensitive variable in order to minimize the risk.Keywords: infrastructure development, toll road, payback period, NPV, IRR